STYPTIC AND WOUND HEALING PROPERTIES OF SIDDHA MEDICINAL PLANTS – A REVIEW. - S. MERISH,; M. TAMIZHAMUTHU,; THOMAS M. WALTER, (International Journal of Pharma and Bio Sciences, 2014)
Traditional Siddha system of Medicine is widely practiced in Tamilnadu and Tamil speaking areas of the World. With the specialty as one of the World’s ancient Traditional systems of Medicine, its importance is being felt and widely discussed nowa-days. Apart from its tremendous healing properties, it is also alleged of not having remedies for emergencies such as Cardiac conditions, acute respiratory conditions, bleeding disorders etc. On the other hand, such conditions have always been dealt by our forefathers’ even centuries back. In olden days the Siddhars’ (founders of Siddha Medicine) used lots of herbs to treat cardiac and respiratory conditions, heal wounds, treat Snake bites, Scorpion bite, dreaded diseases like Cancer and STD/VD etc and documented them in the form of Palm leaf manuscripts, stone and copper scriptures etc.. With the advancement of Medicine, the treatment options and parameters have changed, but the concepts that our ancestors followed so far remains in the old texts and literatures. Nowadays due to modern civilization, such age old practices are put in the dark and often forgotten. So the Authors of this review paper has chosen this topic and listed out the commonly identifiable, easily available, cost effective herbs having styptic action and wound healing properties as per the Siddha traditional literatures. In addition scientific data in the form of In-vivo studies already done in the selected plants have also been reviewed.